A formaldehyde MEMS gas sensor based on PdRh-loaded SnO2 multi-shell structure and its preparation method

By loading PdRh nanoparticles on the SnO2 multi-shell structure, a high-sensitivity MEMS gas sensor was prepared, which solved the problem of time-consuming and labor-intensive formaldehyde detection and expensive equipment in the prior art, and achieved efficient detection of ppb-level formaldehyde.

CN114166899BActive Publication Date: 2025-04-01SHANGHAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111406436.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-24
Publication Date
2025-04-01
Estimated Expiration
2041-11-24

AI Technical Summary

Technical Problem

The prior art requires high professional knowledge of inspectors, time-consuming and labor-intensive, complex analysis of test results, and expensive experimental equipment, low real-time analysis, making it difficult to achieve real-time on-site detection.

Method used

A MEMS gas sensor with PdRh loaded SnO2 multi-shell structure was used to prepare SnO2 multi-shell hollow spheres by hydrothermal method and hard template method, and load PdRh nanoparticles on its surface to improve gas-sensitive response and sensitivity.

Benefits of technology

It realizes detection of ppb-level formaldehyde, improves reaction speed and sensitivity, is simple in process and low in cost, is suitable for mass production, and has important application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114166899B_ABST
    Figure CN114166899B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gas sensors, in particular to a formaldehyde MEMS gas sensor based on a PdRh-loaded SnO2 multi-shell structure and a preparation method thereof, wherein a carbon ball template is prepared by a hydrothermal method, a SnO2 multi-shell hollow sphere is prepared by a hard template method, and the PdRh-loaded SnO2 multi-shell hollow sphere is prepared by placing the prepared material in a mortar, dripping an adhesive into the mortar and grinding for 5 to 10 minutes to obtain a viscous slurry which is coated on a bottom with a Pt interdigital electrode, and after drying, the obtained MEMS device is placed on a base with heating and test electrodes and aged at a voltage of 1.5V for 24 to 72 hours. Compared with the prior art, the present invention adopts a PdRh bimetal to modify the SnO2 multi-shell hollow sphere, and prepares a low-power MEMS formaldehyde gas sensor with good consistency in gas-sensitive performance, thereby improving the response, reaction speed and sensitivity of the sensor and being able to detect formaldehyde concentrations at the ppb level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas sensors, in particular to a formaldehyde MEMS gas sensor based on a PdRh-loaded SnO2 multi-shell structure and a preparation method thereof. Background Art

[0002] Formaldehyde is a typical volatile organic compound with high reactivity and low cost. It has been widely used in many fields closely related to daily life, such as plastic production, detergents, preservatives, wood processing, medicine and food preservation. However, formaldehyde is extremely harmful to the human body and is considered to be one of the most important air pollutants in residential and industrial environments that pose a major threat to human health. Therefore, the detection of formaldehyde is one of the important and necessary tasks in various fields.

[0003] Existing technologies have developed a variety of formaldehyde analysis and detection methods, including electrochemistry, high performance liquid chromatography, gas chromatography, polarography, and fluorescence. However, these methods require high professional knowledge and literacy of inspectors, are time-consuming and labor-intensive, and the analysis methods of test results are complex. The experimental equipment involved is expensive and the real-time analysis is low. Most of them are only suitable for laboratory testing and are difficult to achieve real-time on-site detection. Therefore, it is very important to develop an accurate, reliable, effective, convenient, and fast method for real-time monitoring of formaldehyde.

[0004] Gas sensors based on metal oxide semiconductors have unique advantages such as low cost, easy operation, fast response and recovery speed, and high physical and chemical stability. The difference in the morphology of metal oxide semiconductor sensitive materials has a great influence on the gas sensing performance. Therefore, the gas sensing performance can be improved by synthesizing sensitive materials with different morphologies. The multi-shell hollow structure in the existing morphology has high specific surface area, low density, good surface permeability and high interface charge transfer efficiency. The gas sensors prepared with it have high sensitivity and are widely used in the detection and prediction of various combustible gases, environmental pollution gases, industrial waste gases and harmful gases. In addition, precious metals are modified on the surface of metal oxide semiconductor sensitive materials, and the catalytic effect or electronic sensitization effect of the precious metals are used to effectively promote surface reactions, thereby improving the response of the sensor.

[0005] Therefore, the present invention designs a formaldehyde MEMS gas sensor based on a PdRh-loaded SnO2 multi-shell structure and a preparation method thereof, which improves the reaction speed and sensitivity and can detect formaldehyde concentrations at the ppb level. The method is simple and easy, low-cost, and has low equipment requirements. It can improve the gas-sensitive response of the gas sensor to formaldehyde gas, is suitable for mass production, and has important application value. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a formaldehyde MEMS gas sensor based on a PdRh-loaded SnO2 multi-shell structure and a preparation method thereof, so as to improve the reaction speed and sensitivity and be able to detect formaldehyde concentrations at the ppb level. The method is simple and easy, low in cost, and has low equipment requirements. It can improve the gas-sensitive response of the gas sensor to formaldehyde gas, is suitable for mass production, and has important application value.

[0007] In order to achieve the above object, the present invention provides a formaldehyde MEMS gas sensor based on a PdRh-loaded SnO2 multi-shell structure and a preparation method thereof, comprising the following steps:

[0008] S1: Prepare carbon sphere template by hydrothermal method, prepare 60mL of 0.1-0.3M sucrose solution and place it in a 100mL reactor, perform hydrothermal reaction at 150-200℃ for 8-12h, cool naturally to room temperature, collect the dark brown product in the reactor, wash it with deionized water and ethanol alternately for 3-5 times, and dry it in a constant temperature drying oven at 60-90℃ for 8-12h for later use;

[0009] S2: SnO2 multi-shell hollow spheres were prepared by hard template method. First, 30 mL of 1-3 M hydrated tin tetrachloride (SnCl4·5H2O) solution was prepared, 0.6-1.5 g of carbon spheres were added, ultrasonic dispersion was performed for 15-30 min, magnetic stirring was continued for 4-8 h, vacuum filtration was performed, deionized water was washed 3-5 times, and the sample was dried at 60-90 °C for 8-12 h. The dried sample was heated to 500 °C at a rate of 1-10 °C / min and kept at this temperature for 1 h, and then naturally cooled to room temperature to obtain SnO2 multi-shell hollow spheres.

[0010] S3: Preparation of PdRh-loaded SnO2 multi-shell hollow spheres. First, weigh 100-200 mg SnO2 multi-shell hollow spheres and add them to 10 mL of distilled water. Ultrasonicate for 5-10 min to fully disperse them. Then, take 0.01-0.03 mmol H2PdCl4 and RhCl3·3H2O and add them to the mixed solution. Then, add 1 mL of AA solution (0.1 M) and react at room temperature for 3 h. The product is collected by centrifugation and washed with distilled water for 3-5 times. Finally, it is dried at 60°C for 12 h to obtain PdRh-loaded SnO2 multi-shell hollow spheres.

[0011] S4: Put the prepared PdRh-loaded SnO2 multi-shell hollow sphere material into a mortar, drop an adhesive into it, grind it for 5 to 10 minutes to obtain a viscous slurry, take a small amount of the slurry with a small brush, apply it on the bottom of the Pt interdigital electrode, and then dry it at room temperature to obtain a MEMS device with a sensitive layer of PdRh-loaded SnO2 material. Finally, place the obtained MEMS device on a base with a heating electrode and a test electrode and age it at a voltage of 1.5V for 24 to 72 hours to obtain a formaldehyde gas sensor based on PdRh-loaded SnO2 multi-shell hollow sphere material.

[0012] Compared with the prior art, the present invention uses PdRh bimetal to modify the surface of SnO2 multi-shell hollow spheres, prepares a low-power MEMS formaldehyde gas sensor with good consistency in gas-sensitive performance, improves the response of the gas sensor, improves the reaction speed and sensitivity, and can detect formaldehyde concentrations at the ppb level. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is the XRD diagram of the SnO2 multi-shell hollow sphere material prepared in the present invention.

[0014] Figure 2 TEM images of single-layer, double-layer and multi-layer SnO2 hollow sphere materials prepared in the present invention.

[0015] Figure 3 These are the TEM and HRTEM images of the PdRh-loaded SnO2 multi-shell hollow sphere material prepared in the present invention.

[0016] Figure 4 This is a response diagram of the PdRh-loaded SnO2 multi-shell hollow sphere material prepared in the present invention to formaldehyde at different working temperatures.

[0017] Figure 5 The graphs and linear fitting curves are the response diagrams of the PdRh-loaded SnO2 multi-shell hollow sphere material prepared in the present invention to formaldehyde of different concentrations at 200°C.

[0018] Figure 6 The phase response recovery curve of the PdRh-loaded SnO2 multi-shell hollow sphere material prepared in the present invention to formaldehyde at 200°C. DETAILED DESCRIPTION

[0019] The present invention will now be further described with reference to the accompanying drawings.

[0020] See also Figure 1-5 The present invention provides a formaldehyde MEMS gas sensor based on a PdRh-loaded SnO2 multi-shell structure and a preparation method thereof, comprising the following steps:

[0021] S1: Prepare carbon sphere template by hydrothermal method, prepare 60mL of 0.1-0.3M sucrose solution and place it in a 100mL reactor, perform hydrothermal reaction at 150-200℃ for 8-12h, cool naturally to room temperature, collect the dark brown product in the reactor, wash it with deionized water and ethanol alternately for 3-5 times, and dry it in a constant temperature drying oven at 60-90℃ for 8-12h for later use;

[0022] S2: SnO2 multi-shell hollow spheres were prepared by hard template method. First, 30 mL of 1-3 M hydrated tin tetrachloride (SnCl4·5H2O) solution was prepared, 0.6-1.5 g of carbon spheres were added, ultrasonic dispersion was performed for 15-30 min, magnetic stirring was continued for 4-8 h, vacuum filtration was performed, deionized water was washed 3-5 times, and the sample was dried at 60-90 °C for 8-12 h. The dried sample was heated to 500 °C at a rate of 1-10 °C / min and kept at this temperature for 1 h, and then naturally cooled to room temperature to obtain SnO2 multi-shell hollow spheres.

[0023] S3: Preparation of PdRh-loaded SnO2 multi-shell hollow spheres. First, weigh 100-200 mg of SnO2 multi-shell hollow spheres and add them to 10 mL of distilled water. Ultrasonicate for 5-10 min to fully disperse them. Then, add 0.01-0.03 mmol of H2PdCl4 and RhCl3·3H2O to the mixed solution. Then, add 1 mL of AA solution (0.1 M). React at room temperature for 3 h. Collect the product by centrifugation and wash it with distilled water for 3-5 times. Finally, dry it at 60 ° C for 12 h to obtain PdRh-loaded SnO2 multi-shell hollow spheres.

[0024] S4: Put the prepared PdRh-loaded SnO2 multi-shell hollow sphere material into a mortar, drop an adhesive into it, grind it for 5 to 10 minutes to obtain a viscous slurry, take a small amount of the slurry with a small brush, apply it on the bottom of the Pt interdigital electrode, and then dry it at room temperature to obtain a MEMS device with a sensitive layer of PdRh-loaded SnO2 material. Finally, place the obtained MEMS device on a base with a heating electrode and a test electrode and age it at a voltage of 1.5V for 24 to 72 hours to obtain a formaldehyde gas sensor based on PdRh-loaded SnO2 multi-shell hollow sphere material.

[0025] Embodiment 1:

[0026] Carbon nanospheres were prepared by a hydrothermal method. 0.3 M sucrose solution was dissolved in 60 mL of deionized water to obtain a transparent solution, which was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel reactor. The reactor was placed in an electric oven at 200°C for hydrothermal reaction for 12 hours and naturally cooled to room temperature. The dark brown product was collected by centrifugation and washed with deionized ethanol and deionized water, respectively, and then dried at 90°C overnight to obtain a carbon sphere template.

[0027] SnO2 multi-shell hollow spheres were prepared by the hard template method. First, 30 mL of 1.5 M hydrated tin tetrachloride (SnCl4·5H2O) solution was prepared, 1.5 g of carbon spheres were added, and ultrasonic dispersion was performed for 30 min. Then, magnetic stirring was continued for 8 h, vacuum filtration was performed, and the sample was washed with deionized water for 5 times and dried at 90 °C for 12 h. Finally, the dried sample was heated to 500 °C at a rate of 10 °C / min, kept warm for 1 h, and naturally cooled to room temperature to obtain SnO2 multi-shell hollow spheres.

[0028] Preparation of PdRh-loaded SnO2 multi-shell hollow spheres: first, weigh 200 mg SnO2 multi-shell hollow spheres and add them to 10 mL of distilled water, and ultrasonicate for 10 min to fully disperse them. Then, add 0.03 mmol H2PdCl4 and RhCl3·3H2O to the mixed solution, and then add 1 mL AA solution (0.1 M). React at room temperature for 3 h, collect the product by centrifugation and wash it with distilled water for 3 to 5 times, and finally dry it at 60°C for 12 h to obtain PdRh-loaded SnO2 multi-shell hollow spheres.

[0029] The prepared PdRh loaded SnO2 multi-shell hollow sphere material is placed in a mortar, an adhesive is dropped into it, and it is ground for 5 to 10 minutes to obtain a viscous slurry. A small amount of the slurry is taken with a small brush and coated on the bottom of the Pt interdigital electrode, and then it is dried at room temperature to obtain a MEMS device with a sensitive layer of PdRh loaded SnO2 material. Finally, the obtained MEMS device is placed on a base with a heating electrode and a test electrode and aged at a voltage of 1.5V for 24 to 72 hours to obtain a formaldehyde gas sensor based on PdRh loaded SnO2 multi-shell hollow sphere material.

[0030] like Figure 2 As shown, all XRD diffraction peaks marked in the figure are completely consistent with the peaks of the standard spectrum (JCPDS No. 41-1445), belonging to the tetragonal rutile phase of SnO2. There are no obvious other impurity peaks in the figure, indicating that the sample is a single SnO2 phase.

[0031] Embodiment 2:

[0032] Carbon nanospheres were prepared by a hydrothermal method. 0.1 M sucrose solution was dissolved in 60 mL of deionized water to obtain a transparent solution, which was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel reactor. The reactor was placed in an electric oven at 150°C for hydrothermal reaction for 8 hours and naturally cooled to room temperature. The dark brown product was collected by centrifugation and washed with deionized ethanol and deionized water, respectively, and then dried at 60°C overnight to obtain a carbon sphere template.

[0033] SnO2 multi-shell hollow spheres were prepared by hard template method. First, 30mL of 2.0M hydrated tin tetrachloride (SnCl4·5H2O) solution was prepared, 0.6g of carbon spheres were added, and ultrasonic dispersion was carried out for 15min. Then, magnetic stirring was continued for 4h, vacuum filtration was carried out, deionized water was washed three times, and the sample was dried at 60℃ for 8h. Finally, the dried sample was heated to 500℃ at a rate of 1℃ / min, kept warm for 1h, and naturally cooled to room temperature to obtain SnO2 multi-shell hollow spheres.

[0034] Preparation of PdRh-loaded SnO2 multi-shell hollow spheres: first, weigh 100 mg SnO2 multi-shell hollow spheres and add them to 10 mL of distilled water, and ultrasonicate for 5 minutes to fully disperse them. Then, take 0.01 mmol H2PdCl4 and RhCl3·3H2O and add them to the above mixed solution. Then, add 1 mL AA solution (0.1 M) and react at room temperature for 3 hours. The product is collected by centrifugation and washed with distilled water for 3 to 5 times. Finally, it is dried at 60°C for 12 hours to obtain PdRh-loaded SnO2 multi-shell hollow spheres.

[0035] The prepared PdRh loaded SnO2 multi-shell hollow sphere material is placed in a mortar, an adhesive is dropped into it, and it is ground for 5 to 10 minutes to obtain a viscous slurry. A small amount of the slurry is taken with a small brush and coated on the bottom of the Pt interdigital electrode, and then it is dried at room temperature to obtain a MEMS device with a sensitive layer of PdRh loaded SnO2 material. Finally, the obtained MEMS device is placed on a base with a heating electrode and a test electrode and aged at a voltage of 1.5V for 24 to 72 hours to obtain a formaldehyde gas sensor based on PdRh loaded SnO2 multi-shell hollow sphere material.

[0036] like Figure 1 As shown, all XRD diffraction peaks marked in the figure are completely consistent with the peaks of the standard spectrum (JCPDS No. 41-1445), belonging to the tetragonal rutile phase of SnO2. There are no obvious other impurity peaks in the figure, indicating that the sample is a single SnO2 phase.

[0037] Embodiment 3:

[0038] Carbon nanospheres were prepared by a hydrothermal method. 0.2 M sucrose solution was dissolved in 60 mL of deionized water to obtain a transparent solution, which was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel reactor. The reactor was placed in an electric oven at 180°C for hydrothermal reaction for 9 hours and naturally cooled to room temperature. The dark brown product was collected by centrifugation and washed with deionized ethanol and deionized water, respectively, and then dried at 80°C overnight to obtain a carbon sphere template.

[0039] SnO2 multi-shell hollow spheres were prepared by hard template method. First, 30mL of 3.0M hydrated tin tetrachloride (SnCl4·5H2O) solution was prepared, 1.0g of carbon spheres was added, and ultrasonic dispersion was carried out for 20min. Then, magnetic stirring was continued for 6h, vacuum filtration was carried out, deionized water was washed 4 times, and the sample was dried at 80℃ for 10h. Finally, the dried sample was heated to 500℃ at a rate of 5℃ / min, kept warm for 1h, and naturally cooled to room temperature to obtain SnO2 multi-shell hollow spheres.

[0040] Preparation of PdRh-loaded SnO2 multi-shell hollow spheres: first, weigh 150 mg SnO2 multi-shell hollow spheres and add them to 10 mL of distilled water, and ultrasonicate for 8 minutes to fully disperse them. Then, add 0.02 mmol H2PdCl4 and RhCl3·3H2O to the mixed solution, and then add 1 mL AA solution (0.1 M). React at room temperature for 3 hours, collect the product by centrifugation and wash it with distilled water for 3 to 5 times, and finally dry it at 60°C for 12 hours to obtain PdRh-loaded SnO2 multi-shell hollow spheres.

[0041] The prepared PdRh loaded SnO2 multi-shell hollow sphere material is placed in a mortar, an adhesive is dropped into it, and it is ground for 5 to 10 minutes to obtain a viscous slurry. A small amount of the slurry is taken with a small brush and coated on the bottom of the Pt interdigital electrode, and then it is dried at room temperature to obtain a MEMS device with a sensitive layer of PdRh loaded SnO2 material. Finally, the obtained MEMS device is placed on a base with a heating electrode and a test electrode and aged at a voltage of 1.5V for 24 to 72 hours to obtain a formaldehyde gas sensor based on PdRh loaded SnO2 multi-shell hollow sphere material.

[0042] like Figure 1 As shown, all XRD diffraction peaks marked in the figure are completely consistent with the peaks of the standard spectrum (JCPDS No. 41-1445), belonging to the tetragonal rutile phase of SnO2. There are no obvious other impurity peaks in the figure, indicating that the sample is a single SnO2 phase.

[0043] like Figure 2 As shown, 2a, 2b, and 2c are transmission electron microscope TEM photos of the SnO2 hollow sphere semiconductor materials obtained in Example 1, Example 2, and Example 3, respectively. When the concentration of SnCl4·5H2O is 2M, the synthesized SnO2 nanomaterials all have a multi-shell hollow spherical regular morphology, with consistent grain size and uniform wall thickness. Therefore, the number of layers, grain size distribution, and wall thickness distribution of the SnO2 nano hollow spheres can be controlled by controlling the concentration of SnCl4·5H2O.

[0044] like Figure 3As shown in the figure, the transmission electron microscope TEM image and HRTEM image of the SnO2 hollow sphere semiconductor material prepared in this embodiment are shown in the figure. Figure 3 (b) Confirmation of the successful loading of Pd and Rh in SnO2 multilayer shell hollow sphere samples.

[0045] like Figure 4 As shown in FIG. 1 , the response value of the formaldehyde MEMS gas sensor obtained in this embodiment varies with the operating temperature. Figure 4 It can be seen that the gas sensor obtained in this embodiment shows the best response when the working temperature is 200°C.

[0046] like Figure 5 As shown in FIG. 1 , the voltage of the formaldehyde MEMS gas sensor obtained in this embodiment varies with the formaldehyde gas concentration. Figure 5 It can be seen that the voltage of the gas sensor obtained in this embodiment increases with the increase of formaldehyde concentration, showing a linear relationship, and the detection limit is as low as 50 ppb.

[0047] like Figure 6 As shown in the figure, it is the response recovery curve of the gas sensor prepared in this embodiment. The response time is defined as the time when the voltage on the load resistor RL changes from U0 to U0+90% (U X -U0) and the recovery time is the time required for the voltage of the load resistor RL to recover from UX to U0+10% (U X -U0) time, from Figure 5 It can be seen that the gas sensor obtained in this embodiment has a good response to formaldehyde, and the response-recovery time is short, which is 5s and 7s respectively.

[0048] The above are only preferred embodiments of the present invention, which are only used to help understand the method and core ideas of the present application. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

[0049] The present invention solves the problems of the prior art in that the professional knowledge and literacy of inspectors are high, the technology is time-consuming and laborious, the test result analysis method is complex, the experimental equipment involved is expensive and the real-time analysis is low, and most of them are only suitable for laboratory detection and are difficult to achieve real-time on-site detection. When PdRh nanoparticles are loaded on SnO2 multi-shell hollow sphere materials, the lattice defects introduced due to lattice mismatch are beneficial to improving the gas-sensitive response of the gas-sensitive material, and the gas sensor based on PdRh-loaded SnO2 multi-shell hollow sphere materials has a lower detection limit and can achieve ppb level formaldehyde detection. The present invention has a simple process, a small size of the prepared formaldehyde gas sensor, a fast response recovery speed, and a low cost, and is suitable for mass production, and has important application value.

Claims

1. A method for preparing a formaldehyde MEMS gas sensor based on a PdRh-loaded SnO2 multi-shell structure, characterized in that The following steps are included: S1: Prepare carbon sphere template by hydrothermal method, prepare 60 mL of 0.1-0.3 M sucrose solution and place it in a 100 mL reactor, hydrothermally react at 150-200 °C for 8-12 h, cool naturally to room temperature, collect the dark brown product in the reactor, wash it with deionized water and ethanol alternately for 3-5 times, and dry it in a constant temperature drying oven at 60-90 °C for 8-12 h for use; S2: SnO2 multi-shell hollow spheres were prepared by hard template method. First, 30 mL of 1-3 M hydrated tin tetrachloride (SnCl4·5H2O) solution was prepared, 0.6-1.5 g of carbon spheres were added, ultrasonic dispersion was performed for 15-30 min, magnetic stirring was continued for 4-8 h, vacuum filtration was performed, deionized water was washed 3-5 times, and the sample was dried at 60-90 °C for 8-12 h. The dried sample was heated to 500 °C at a rate of 1-10 °C / min and kept for 1 h, and then naturally cooled to room temperature to obtain SnO2 multi-shell hollow spheres. S3: Preparation of PdRh-loaded SnO2 multi-shell hollow spheres. First, weigh 100-200 mg SnO2 multi-shell hollow spheres and add them to 10 mL of distilled water. Ultrasonicate for 5-10 min to fully disperse them. Then, add 0.01-0.03 mmol H2PdCl4 and RhCl3·3H2O to the mixed solution. Then, add 1 mL of 0.1 M AA solution. React at room temperature for 3 h. Collect the product by centrifugation and wash it with distilled water for 3-5 times. Finally, dry it at 60 ° C for 12 h to obtain PdRh-loaded SnO2 multi-shell hollow spheres. S4: Put the prepared PdRh-loaded SnO2 multi-shell hollow sphere material into a mortar, drop an adhesive into it, grind it for 5 to 10 minutes to obtain a viscous slurry, take a small amount of the slurry with a small brush, apply it on the bottom of the Pt interdigital electrode, and then dry it at room temperature to obtain a MEMS device with a sensitive layer of PdRh-loaded SnO2 material. Finally, place the obtained MEMS device on a base with a heating electrode and a test electrode and age it at a voltage of 1.5V for 24 to 72 hours to obtain a formaldehyde gas sensor based on PdRh-loaded SnO2 multi-shell hollow sphere material.

Citation Information

Patent Citations

  • Graded core-shell SnO2 microspheres as well as preparation method and application thereof

    CN110606504A